Perancangan Aplikasi Mobile tentang Etika Digital pada Pola Asuh Anak Usia Remaja Awal - Adnyana Hrumsari; Achmad Syarief (Jurnal Sosioteknologi, 2023)
COVID-19 has led to a shift from offline to online teaching and learning in schools, increasing screen time for early adolescents. This increases exposure to non-educational content, enabling cyberbullying, pranks, pornography, and hoaxes. Parents play a crucial role in digital parenting by understanding and regulating digital activities, often using parental control apps for safety reasons. For security reasons, many parents begin to use parental control apps to monitor the use of gadgets. This study aims to identify parenting approaches to introduce digital ethics and then design apps that can accommodate parenting styles in early-adolescent teenagers. The research used quantitative and qualitative methods. The design method used was the Four Basic Activities of Interaction Design. The Parentika app features were designed based on the TOSS (Teen Online Safety Strategies) framework, considering the balance between parental control and self-moderation. Based on the results of the Parentika app’s evaluation by users, it is proven to be excellent based on effectiveness, efficiency, and user satisfaction. Through Parentika apps, parents can participate in educating themselves about digital ethics. In addition to being digital mentors, it is hoped that parents can also become role models for early adolescence.